Metabolism-Based Herbicide Resistance, the Major Threat Among the Non-Target Site Resistance Mechanisms. (1st August 2020) - Rigon, Carlos; Gaines, Todd; Küpper, Anita; Dayan, Franck
Evolution of resistance to pesticides is a problem challenging the sustainability of global food production. Resistance to herbicides is driven by the intense selection pressure imparted by synthetic herbicides on which we rely to manage weeds. Target-site resistance (TSR) mechanisms involve changes to the herbicide target protein and provide resistance only to herbicides within a single mechanism of action. Non-target site resistance (NTSR) mechanisms reduce the quantity of herbicide reaching the target site and/or modify the herbicide. NTSR mechanisms include reduced absorption and/or translocation, increased sequestration, and enhanced metabolic degradation. Of these diverse mechanisms contributing to NTSR, metabolism-based herbicide resistance represents a major threat because it can impart resistance to herbicides from varied chemical classes across any number of mechanisms of action.